The Rational Behavior Concept in Islam and Policy Framework Perspectives - Dimas Bagus Wiranata Kusuma; Masyhudi Muqorrobin; Charafeddine Krouchj; Nur Jamaluddin (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2013)
The primary notion of preference and utility under Islamic perspective is to restore the consumer behavior in accordance with the concept of maslahah. The paper basically tries to apply the concept of maslahah by specifically defining it into Good Deeds (G) and Bad Deeds (B) concepts subject to a certain limit of Ability (A). Hicksian and Marshallian demand functions are used to model maslahah under Islamic banking practices in Indonesia and Malaysia. The paper employs several variables to gauge the Maslahah (M) as well as Ability (A) function. Empirically, the variables used to measure Maslahah function are deposit, financing, and rate of return variables. In addition, Cobb-Douglas (CD) utility function is utilized to model the maslahah. Indonesia seems to have bigger maslahah compared with Malaysia according to Islamic Banking practices, but more effort should be persistently undertaken by Indonesian Islamic Banks to retain a certain level of maslahah instead of Malaysia. Since maslahah is seen as the manifestation of Good Effort (Eg), some policies frameworks could be suggested, namely regarding shariah framework, tax regime, and someoutstanding issues and challenges for Islamic banking development.